The coordinate structures in a corpus of New Age talks: man and woman/woman and man - Vefali, Guelsen Musayeva; Erdentug, Fulya (De Gruyter Mouton, 2010)
In this article we explore language in a specialized corpus of gender-related talks by Osho, one of the founders of the New Age postmodern movements. Specifically, we examine the coordinate structures man and woman and woman and man which, unlike the gendered lexical items man/woman, have not received attention in the previous language and gender studies. For our research purposes, we adapt a new methodological framework (Baker et al. 2008) integrating corpus analysis and qualitative analysis. The qualitative analysis of the corpus evidence (frequency, collocates, and concordances) in relation to gender construal in the specialized corpus seems to indicate a newly emerging semantic profile of the coordinate structures with man and woman, as well as a new, holistic gender identity which is in line with the holistic views of the New Age and Osho movement.
Keywords: man and woman; woman and man; corpus evidence; gender; New Age; Osho